2017
DOI: 10.4103/0974-2069.197053
|View full text |Cite
|
Sign up to set email alerts
|

A pediatric echocardiographic Z-score nomogram for a developing country

Abstract: Background:Almost all presently available pediatric echocardiography Z-score nomograms are based on Western data. They may not be a suitable reference standard for assessing the sizes of cardiac structures of children from developing countries.Objective:This study's objective was to collect normative data of 21 commonly measured cardiovascular structures using M-mode and two-dimensional echocardiography in Indian children aged between 4 and 15 years and to derive Z-score nomograms for each.Subjects and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…We thank the author for his keen interest in our study[ 1 ] and his valuable response for the same. [ 2 ] We read with utmost interest the four issues put forth by the author and wish to provide relevant clarifications.…”
mentioning
confidence: 99%
“…We thank the author for his keen interest in our study[ 1 ] and his valuable response for the same. [ 2 ] We read with utmost interest the four issues put forth by the author and wish to provide relevant clarifications.…”
mentioning
confidence: 99%
“…LA diameter references were established in twelve studies, six of which were conducted in US American children [ 16 , 28 , 30 , 38 , 39 ]. LA length references were from Indian, Italian and Swedish children and of these, two studies also reported data on LA area [ 5 , 9 , 32 ]. LA volume was derived in four studies and three of these were in US American children (Table 3 ) [ 12 , 14 , 21 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…on the constructing pediatric echocardiographic Z -score nomogram in India. [ 1 ] Apart from a few limitations addressed by the authors, I presume that the following four limitations might additionally cast some suspicions on the study results and possibly introduce bias in the clinical decision-making process.…”
mentioning
confidence: 99%
“…First, in the methodology, the authors stated that various echocardiographic measurements were expressed in relation to body surface area (BSA) calculated by Haycock's formula (BSA = weight 0.5378 × height 0.3964 × 0.024265). [ 1 ] It is worthy to mention that various formula are present in the clinical settings to calculate BSA, namely, Boyd, Mosteller, Gehan and George, Haycock, and Dubois-DuBois. Clinical evaluation revealed the different performance of each BSA estimation method in certain pediatric population.…”
mentioning
confidence: 99%
See 1 more Smart Citation